Analisis Produksi dan Faktor Produksi Usaha Tani Terpadu Tanaman Padi dan Ternak Sapi di Nagari Taram Kecamatan Harau - Mukhlis; Riva Hendriani; Regia Indah Kemala Sari; Nila Sari (Politeknik Negeri Lampung., 2022)
Green Agriculture can be developed through an integrated farming system of crop and livestock. The purpose of this research is to know the description of production and production factors of integrated farming of rice and cattle. This study uses a descriptive method, which is carried out in Lima Puluh Kota Regency, precisely in Harau District. The selection of the research area was carried out in purposive method. The study was conducted in April - June 2022. Determination of the research sample using the snowball sampling method. Collecting data using interview method using questionnaires to obtain primary data and documentation method to obtain secondary data. The data analysis method used descriptive analysis using a triangulation technique approach that tested the validity of the data with methods, sources, and theories. The amount of rice production produced by farmers in integrated farming of rice and cattle in the study area ranged from 3,300 - 16,200 Kg. However, the average amount of rice production produced is 6,940.88 Kg. The production factors in rice farming, integrated farming of rice and cattle, include: paddy fields, cowsheds, rice seeds, cattle seeds/nursery, organic fertilizers, inorganic fertilizers, cattle feed, pesticides, drugs and vitamins. cattle, labor and capital.